Impact of Radial Compared to Femoral Access on Major Bleeding and Mortality in ACS Patients Undergoing PCI - Ahsan Ali, Sardar Bilal Mehboob Abbasi, Muhammad Akram Khan, Madia Ayaz Malik, Shumaila Israr, Muhammad Ali Zaib Khan, Effat Zahrah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Bleeding complications after percutaneous coronary intervention (PCI) remain a major determinant of morbidity and mortality in acute coronary syndrome (ACS). Vascular access site is a critical factor influencing these outcomes. Objective: To compare the incidence of major bleeding and in-hospital mortality between radial and femoral access in patients with ACS undergoing PCI. Methods: This prospective observational study included 345 patients with ACS undergoing PCI at Punjab Institute of Cardiology, Lahore from February 2023 to July 2023. Patients were divided into radial access (n=176) and femoral access (n=169) groups. Demographic characteristics, cardiovascular risk factors, clinical presentation, and procedural details were recorded. Outcomes assessed included major bleeding (BARC 3–5), transfusion requirement, access-site complications, in-hospital mortality, major adverse cardiovascular events (MACE), and hospital stay duration. Results: Baseline characteristics were comparable between groups, though femoral patients were slightly older and more often presented with Killip class II–IV. Major bleeding occurred in 2.8% of radial patients versus 10.7% of femoral patients (p=0.004). Any bleeding was observed in 6.8% of radial versus 17.2% of femoral cases (p=0.002). Transfusion requirements (1.7% vs. 7.1%, p=0.01) and hemoglobin drop ≥3 g/dL (2.3% vs. 8.3%, p=0.01) were significantly lower in the radial group. In-hospital mortality was 4.0% with radial access compared to 10.7% with femoral (p=0.02). MACE occurred in 10.8% of radial versus 22.5% of femoral patients (p=0.004). Mean hospital stay was shorter in the radial group (4.9 vs. 6.1 days, p<0.001). On multivariable analysis, radial access independently reduced the odds of major bleeding (aOR 0.38, 95% CI 0.15–0.91, p=0.03) and mortality (aOR 0.41, 95% CI 0.17–0.97, p=0.04). Conclusion: Radial access significantly reduces bleeding complications, mortality, and major adverse cardiovascular events compared to femoral access in ACS patients undergoing PCI. These findings support the adoption of radial access as the preferred strategy to improve short-term outcomes in this high-risk population. Keywords: Acute coronary syndrome, PCI, radial access, femoral access, major bleeding, mortality, MACE